(untitled) (Relevant Tomorrow / Aktualu rytoj, 2025)
Based on research data and sociological surveys, the article examines the markers of Ukrainian history since 2014 through the prism of inclusion/exclusion of historical events, periods, and personalities as the components of state- and nation-building, memory, and the politics of history. The study employs several methodological approaches: a constructivist approach to identity, the concept of the links between historical markers and nation-building and the concept of memory security. The bulk of empirical data for the study is taken from a representative sociological survey conducted in Ukraine in 2022. It focuses on three pillars of Ukrainian national identity of the twentieth century: the Ukrainian Revolution, the Holodomor and World War II, as well as the Russo-Ukrainian War. The results of the study show that since 2014, the politics of Ukrainian history have been dominated by events and personalities of the twentieth century. The dominance of the Holodomor in collective memory of Ukrainians indicates its greater importance compared to WWII. The study also argues that the claim about “fragmented” and “contested” Ukrainian memory is largely outdated; however, further research is needed to understand the systematic transformations of Ukrainian identity, especially after the Russian “hybrid war,” which in February 2022 turned into open military aggression against Ukraine.